The association between gestational hypothyroidism in pregnant women with preeclampsia, maternal liver function indicators, and neonatal birth weight: a study in Chinese pregnant women - Zhang, Fang; Hua, Qing; You, Xiaoyan; Shi, Fenglian; Zhou, Yadan; Xu, Xia; Tian, Xiaona; Tian, Gang; Li, Li (Frontiers in Endocrinology, 2025)
Birth weight serves as a critical indicator of neonatal survival. Preeclampsia represents a serious complication during pregnancy and is closely associated with gestational hypothyroidism (GHT), both of which severely affect neonatal birth weight. Preeclampsia and hypothyroidism during pregnancy are usually accompanied by abnormalities of maternal liver function, which frequently leads to adverse pregnancy outcomes including low birth weight (LBW). This retrospective study utilized data from 420 cases of patients with preeclampsia who underwent prenatal examinations and delivery at department of Obstetrics. The association between preeclampsia combined with GHT in pregnancy, maternal liver function and neonatal birth weight was estimated using generalized linear model (GLM), and the potential partial mediating effects of maternal liver function were assessed through mediating models. Among pregnant women with preeclampsia, 11.0% had GHT, and the median (interquartile range) birth weight of all neonates was 2990.0 (2541.3, 3368.8) grams. Neonates born to pregnant women who had preeclampsia combine with GHT showed a higher incidence of LBW (χ²=22.13, P< 0.001), exhibited a significantly lower birth weight compared to those born to women with preeclampsia alone (β=-258.53;95%CI:-398.56, -118.50). Additionally, maternal alanine aminotransferase (ALT) levels were found to partially mediate this association (indirect effect:-50.85, 95%CI:-101.07, -15.07). The findings of this study indicate that compared with pregnant women with preeclampsia alone, neonates born to pregnant women suffering from preeclampsia combined with GHT have significantly lower birth weights, with maternal ALT levels acting as a potential partial mediator in this association. These results provide an important reference for clinicians to monitor thyroid and liver function in patients with preeclampsia.